Inspeksi dan Pemeliharaan Peralatan Dental Unit di Puskesmas dalam Masa Pandemi Covid-19 - jaya, indra; Muhsen, Irma; yanti, Fitri; Mulyani, Sri; Azmi, Zul (Research and Social Study Institute, 2023)
Covid-19 is a virus that can spread through the mouth, and attack the lungs so that the patient will experience respiratory problems. The effect caused by the virus is the thickening of the fluid in the lungs, causing the sufferer to experience difficulty in breathing. The purpose of this service is to socialize, inspect and maintain dental unit equipment as a medical support tool at the Kuta Alam Health Center in Banda Aceh City. This activity was carried out during the Covid-19 pandemic. This is done so that dental unit equipment as medical support can be used properly and avoid the spread of the Covid-19 virus. The method used is to provide material to medical staff, to carry out inspections and maintenance of dental unit equipment in the dental and oral service room. The results obtained are an increasing understanding of the covid-19 virus, and understanding the functions and benefits of dental unit devices for efficiency of maintenance cost. The material presented was in great demand by the public and hoped that there would be a continuation with other topics.